Preparedness to implement "a family physician for every family," which is the magic recipe for cost-effective health care for all: Viewpoint - Sulaiman A Alshammari (Wolters Kluwer Medknow Publications, 2023)
The Saudi Vision 2030 endorsed health-care models emphasizing promotion, prevention, and effective treatment. The 2008 World Health Organization report, "Primary Health Care: Now More Than Ever," also encouraged reform. The objective of this study was to highlight the evidence and benefits of scaling up PHC capacity to implement "a family physician for every family" model. PubMed, Google Scholar, the Saudi digital library, theses, conference proceedings on family medicine, primary care, general practice, family physicians, government reports, policy documents, and press releases in Arabic and English were searched from September 2021 to September 2022. The search terms included: Saudi health care, health-care transformation, family medicine, primary care, general practice, family physician, family doctor, Saudi Arabia, Saudi Vision 2030, phone consultation, virtual clinic, electronic medical records, public-private partnerships, and privatization. Vision 2030 endorses the transformation of the public sector to implement international best practices. Saudi Arabia is ready to implement "a family physician for every family" model to reduce morbidity and mortality from noncommunicable diseases while improving quality and cost-effectiveness. The extensive network of health centers, growing number of family physicians, and advanced digitalization can accelerate this. In addition, mobilizing resources and incentives can optimize health promotion and disease prevention.